AN ANALYSIS OF TEACHER AS MEDIATOR IN EFL CLASS - Nunung Nurhasanah (University of Kuningan, 2014)
Abstract:Â This paper concerned about how criteria of mediator applied in role of the teacher in EFL class and what the most dominant criteria of mediator done by the teacher in EFL class. It was limited to analyze the role of teacher as mediator based on Feuersteinâ€™s Mediated Learning Experience criteria (1980) in Xiongyong et al., (2012). The method was qualitative research by using techniques structured observation and questionnaire that the process of teaching and learning was recorded by video then it was transcribed to identify the existence of criteria of mediator in the class. It also used observation worksheet to show the existence of criteria of mediator during three times observation. Based on the findings of the research, the teacher applied all criteria of mediator well which shared intention was the most dominant criteria that was done by the teacher in the class with percentage 87%. It means that the teacher made instructions clearly during the learning so that the students could understand about the lesson and present their tasks well.Keywords: role of teacher, mediator, mediated learning experience, EFL class.